Multimodular auxin response controls lateral root development in Arabidopsis - De Smet, Ive (Plant Signal Behav, 2010)
In plants, the phytohormone auxin plays a prominent role in controlling nearly every step in plant growth and development. However, it is unclear how one generic signal such as auxin can be translated in so many diverse developmental responses. Recently, we could show that, next to its well known role in embryogenesis, the auxin response module controlled by the BODENLOS (BDL)/INDOLE-3-ACETIC ACID12 (IAA12)-MONOPTEROS (MP)/AUXIN RESPONSE FACTOR5 (ARF5) pair also plays a role in lateral root development, and that this auxin response succeeds the one controlled by SOLITARY ROOT (SLR)/IAA14-ARF7-ARF19. We conclude that bi- or multimodular response mechanisms might be a general principle of auxin signaling in plants, which provides a genetic framework for a single molecule such as auxin to have many diverse functions.